2021
DOI: 10.1111/iej.13502
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity, cytocompatibility and effect of Bio‐C Temp bioceramic intracanal medicament on osteoblast biology

Abstract: Aim To analyse the antimicrobial and biological properties of a new bioceramic intracanal medicament (Bio‐C Temp), and to compare it with two calcium hydroxide‐based intracanal medicaments (Calen® and UltraCal® XS). Methodology The direct contact and the crystal violet tests were performed to assess the antimicrobial activity of intracanal medicaments against Enterococcus faecalis. The cytocompatibility and the effect of the medication on the biology of the human osteoblast‐like cell line (Saos‐2) were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 39 publications
3
38
0
8
Order By: Relevance
“…In the present study, the null hypothesis was rejected, as significant differences were found between the calcium silicate‐based materials in most of the evaluated parameters. Although previous studies have evaluated BD using similar methodologies (Adl et al, 2019; Farrugia et al, 2018; Marconyak et al, 2015; Ochoa‐Rodrıguez et al, 2019; Ochoa‐Rodriguez et al, 2020; Oliveira et al, 2020; Shokouhinejad et al, 2016; Vallés et al, 2015; Yoldas et al, 2016), few studies have used BCT (Guerreiro et al, 2021; Oliveira et al, 2020; Villa et al, 2020) and BCR (Benetti et al, 2019; Ghilotti et al, 2020; López‐García et al, 2019), which are new ready‐to‐use materials. To assess crown discolouration by these materials in the presence of blood components, a model was designed to simulate the clinical situation of partial pulpotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the null hypothesis was rejected, as significant differences were found between the calcium silicate‐based materials in most of the evaluated parameters. Although previous studies have evaluated BD using similar methodologies (Adl et al, 2019; Farrugia et al, 2018; Marconyak et al, 2015; Ochoa‐Rodrıguez et al, 2019; Ochoa‐Rodriguez et al, 2020; Oliveira et al, 2020; Shokouhinejad et al, 2016; Vallés et al, 2015; Yoldas et al, 2016), few studies have used BCT (Guerreiro et al, 2021; Oliveira et al, 2020; Villa et al, 2020) and BCR (Benetti et al, 2019; Ghilotti et al, 2020; López‐García et al, 2019), which are new ready‐to‐use materials. To assess crown discolouration by these materials in the presence of blood components, a model was designed to simulate the clinical situation of partial pulpotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Other ready‐for‐use silicate‐based materials developed recently are Bio‐C Temp (BCT; Angelus, Londrina, PR, Brazil) and Bio‐C Repair (BCR; Angelus). Both have low cytotoxicity (Ghilotti et al, 2020; Guerreiro et al, 2021; López‐García et al, 2019; Oliveira et al, 2020; Villa et al, 2020), good biocompatibility (Benetti et al, 2019) and biomineralization ability (Benetti et al, 2019; López‐García et al, 2019). BCT was primarily conceived by the manufacturer as an intracanal dressing (Villa et al, 2020) and is also indicated for full pulpotomy (Oliveira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Essa diferença pode estar relacionada com a baixa concentração de HC na pasta Ultracal ® XS, promovendo uma menor liberação de íons nos tecidos e, consequentemente, menor ação antimicrobiana. A pasta Bio-C Temp também mostrou baixa ação antimicrobiana, o que pode estar relacionada a sua baixa alcalinidade e a menor formação de moléculas de HC na reação de hidratação (Guerreiro, et al, 2021). Nesse teste, o Bio-C Temp e Ultracal ® XS tiveram ação antimicrobiana semelhantes.…”
Section: Discussionunclassified
“…As limitações deste estudo in vitro incluem o uso de biofilmes monoespécies de E. faecalis, que são provavelmente mais suscetíveis do que biofilmes multiespécies. Apesar do conhecimento do perfil polimicrobiano das infecções endodônticas, a maioria dos estudos in vitro utilizou biofilmes monoespécies para testar materiais endodônticos, o que possibilitou a comparação de nossos dados com estudos anteriores (Barros, et al, 2014;Tabrizizadeh, et al, 2015;Collares, et al, 2018;Balto, et al, 2020;Guerreiro, et al, 2021).…”
Section: Discussionunclassified
See 1 more Smart Citation